Analisis Pemanfaatan Papan Tulis Digital Interaktif dalam Meningkatkan Motivasi Belajar Siswa Kelas XI SMK Negeri 1 Gunungsitoli Utara - Zega, Yarman; Nduru, Mastawati; Halawa, Noibe; Zega, Imansudi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Low student learning motivation remains a challenge in the learning process because it causes students' active involvement to be less than optimal. One alternative to overcome this problem is the use of interactive digital whiteboards that are able to present material visually, interactively, and participatory so that it is expected to increase learning motivation. This study aims to analyze the use of interactive digital whiteboards in increasing the learning motivation of grade XI students at SMK Negeri 1 Gunungsitoli Utara. The study used a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation with informants consisting of subject teachers and grade XI students, then analyzed using thematic analysis. The results showed that the use of interactive digital whiteboards increased student learning motivation as indicated by increased attention, interest, perseverance, and active participation during learning. The research findings also showed that material visualization, interactive features, and direct feedback created a more engaging learning experience, while the effectiveness of their use was influenced by teacher competence in operating the device and the support of school infrastructure. This study confirms that interactive digital whiteboards are a learning medium that has the potential to increase learning motivation if supported by teacher pedagogical readiness and adequate school facilities.